Participation incentives and the design of voluntary agreements: Special issue on voluntary approaches, competition and competitiveness - Rinaldo Brau; Carlo Carraro; Giulio Golfetto (Fondazione Eni Enrico Mattei (FEEM), 2001)
This paper analyses the conditions under which a group of firms has the incentive to sign a Voluntary Agreement (VA) in order to control its emission flows even in the presence of free-riding by other firms in the industry. For the purpose of this paper it is assumed that free-riders cannot be completely excluded from the expected benefits of the VA, which increase with the number of signatory firms and with the abatement level achieved. The paper focuses on policy design by discussing the features that a VA should possess in order to increase its economic and environmental effectiveness. The results support some important conclusions. First, VAs cannot emerge in the case of a pure public good, i.e. when spillovers are such that all firms benefit from the abatement of the signatory firms. Second, even in the case of partial spillovers, the regulator has to impose a minimum participation constraint for the VA to be signed. In this case, if the minimum participation constraint is met, all firms have an incentive to sign the VA. Third, a VA with a minimum amount of regulation improves welfare with respect to a VA in which firms are free to set their profit maximising abatement level.
Keywords: K32; D21; Q28; 330; Voluntary agreement; voluntary approach; environmental protection; free-riding; emissions tax; Selbstverpflichtung; Umweltbelastung; Trittbrettfahrerverhalten; Ökonomischer Anreiz; Spillover-Effekt; Theorie